ANALISIS PENDAPATAN USAHATANI CABAI RAWIT DI SUKAWATI KECAMATAN SUKAWATI KABUPATEN GIANYAR. - Afrianus Gosardi; Ni Gst.Ag.Gde Eka Martiningsih; Ida Ayu Made Dwi Susanti,; Ni Putu Eka Pratiwi (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2022)
The aim is to determine the amount of income received by cayenne pepper farmers in Sukawati Village, the sampling technique in this study uses the purposive method, Analysis of the data used .namely income analysis by determining the cost and revenue . Farming efficiency is sought by the R/C formula. The results of this study indicate that the income of cayenne pepper farming in Sukawati Village is Rp. 31.315.600 per 27 acre land area, per one farming season or Rp 115.983.000/hectares, with an R/C value of 3.288 this indicates that cayenne pepper farming in Sukawati Village is very efficient and profitable. for the local community, so that it plays a very important role in the income of cayenne pepper farming in Sukawati Village. based on the results of the study, it is recommended that cayenne pepper farming in Sukawati Village maintains the results of its farming by developing better cayenne pepper management procedures.